TAŞINMAZ SATIŞLARINDAKİ KURUMLAR VERGİSİ VE KDV İSTİSNALARININ TAŞINMAZ TİCARETİ VE KİRALANMASI FAALİYETLERİ ÖZELİNDE DEĞERLENDİRİLMESİ - (:unkn) unknown (My University, 2021)
Kurumlar vergisi mükelleflerinin sermaye yapılarının güçlendiril- mesi amacıyla, belirli şartlar altında gayrimenkul satışlarından elde edi- lecek kazançlar için vergi istisnası getirilmiştir. Bu çalışmada; şirket ana sözleşmesinde veya ticaret unvanında faaliyet konusu taşınmaz ticareti ve/veya kiralanması olan ancak bu alanda fiilen iştigal etmeyen kurumla- rın ile ana sözleşmesinde taşınmaz ticareti ve/veya kiralaması bulunma- makla birlikte çok sayıda taşınmaz alım-satımı veya kiralaması yapan kurumların Kurumlar Vergisi Kanunu ve Katma Değer Kanunu’nda yer alan istisna düzenlemeleri karşısındaki durumları vergi idaresinin görüş- leri ve yargı kararları çerçevesinde değerlendirilmiş ve buna ilişkin gö- rüşlerimize yer verilmiştir.

In order to strengthen the capital structures of corporate taxpa- yers, tax exemptions have been introduced for earnings to be obtained from real estate sales under certain conditions. In this study; Corporate Tax Law and Value Added Law of institutions whose field of activity is immovable trade and/or leasing in the company's articles of association or trade name, but which are not actively engaged in this field, and insti- tutions that do not have immovable trade and/or leasing in their articles of association, but which purchase, sell or lease a large number of im- movables. Their situation against the exception regulations in the Tax Administration has been evaluated within the framework of the opinions of the tax administration and judicial decisions, and our views on this issue are included.
EVALUATION OF CORPORATE TAX AND VAT EXCLUSIONS ON IMPROVEMENT SALES SPECIFIC TO REAL ESTATE TRADE AND LEASE